Memorandum of understanding between Universiti Teknologi MARA and Universitas Islam Indonesia / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2018)
Memorandum of understanding on friendship and cooperation for the purpose of promoting mutual understanding and academic, cultural, scientific and personnel exchange.